Perancangan Filter Pasif Pada Gardu Traksi di Stasiun Citayam Guna Mengurangi Efek Distorsi Harmonisa - Putri Jori, Rahmatika Dwi; Sari, Nurwanda; Desliana, Lulu Syahira; Maulidina, Siti; Mardhotillah, Nur Anisa; Arif, Muhammad Rizki; Aini, Nur Syahidah (UNIB Press, 2025)
Electric Rail Trains (KRL) have become the most frequently used transportation mode for daily activities in the community. One of the existing problems within the operation system of Electric Rail Trains (KRL) lies in the current rectification process. During this rectification process, an effect occurs that can cause disturbances in the KRL's electrical system. This resulting effect is the harmonic effect. This study aims to address the problem of power quality degradation in the Electric Rail Train (KRL) at the Citayam Station Traction Substation, which is caused by this harmonic effect. The harmonic effect arises from the process of rectifying alternating current (AC) into direct current (DC) using a silicon rectifier, which can lead to voltage drop, speed reduction, or even the operational stoppage of the KRL.The research method used is quantitative descriptive. The study did not conduct direct measurements but instead used averaged assumption data from three related journals as primary data. The data analyzed were the values of Total Harmonic Distortion (THD) for both current and voltage, particularly focusing on the 5th, 7th, and 11th harmonic orders, which were identified as the highest contributors to the harmonic distortion. To mitigate the harmonics, this study designed a single-tuned passive filter using the ETAP (Electric Transient Analysis Program) software. The design aims to suppress the harmonic distortion, thereby improving the electrical power quality, maintaining the reliability of the traction substation, and optimizing KRL operations. The single-tuned passive filter designed in this research was capable of suppressing harmonics by up to 0.009%.